School library management just the basics - Messner, Patricia A.; Copeland, Brenda S. (Santa Barbara, California Libraries Unlimited, 2012)
"Written in clear, simple language, this book provides information that will help an aide or paraprofessional manage a school library"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: School libraries -- United States -- Administration